Current Advances in Fuel Cell Technology - Masli Irwan Rosli; Mohammed S. Ismail (Energies)
Fuel cell technology is a significant contributor to the global push towards clean energy, offering high efficiency and low emissions ideal for applications such as electric vehicles and stationary power systems [...]